Whole Genome Sequencing For Establishment Of Phylogenetic Position And Discovery Of Miniaturization And Lipid Metabolism Genes In Paedocypris - Sam, Ka Kei (2022)
Paedocypris is the world’s smallest vertebrate with a total length of ≤ 20 mm restricted to acidic freshwater peat swamp environments. The anatomy of Paedocypris is highly modified with developmental truncated characters. The unique miniature phenotypes make the Paedocypris a good model fish to study development and evolution. Three Paedocypris species have been described, including P. micromegethes from Sarawak and another two species, P. progenetica and P. carbunculus from Indonesia. Thus far, Paedocypris has no chromosome-scale genome, with only a draft genome with scaffold N50 ~59-61 kb. In this study, a high-quality chromosome level genome assembly for the P. micromegethes was generated with improved scaffold N50 of 29.8 Mb using a combination of Illumina, PacBio and Hi-C sequencing technologies. Meanwhile, the draft genome for the P. carbunculus was improved with N50 scaffold length of 125 Kb. This study revealed that the small and compact genome sizes of miniature Paedocypris are characterized by a low repeat content, short introns, and a lack of recent genome duplications. Additionally, this study discovered gene loss from the improved genome assemblies, such as fgf8b, mtmr14, scpp3a, scpp3b, scpp6, scpp7 scpp8, gsp37, spp2, and tbx22. Phylogenetic analysis to resolve the contentious taxonomy position of miniaturized cyprinids using mitochondrial 13 protein-coding genes (PCGs) and two ribosomal RNA genes (rRNAs) showed improved supportive values for the sister-group relationship for Paedocypris and Sundadanio to the Danionidae family.